Effective wireless low‐power transmission using a phased array antenna. Issue 2 (February 2015) - Park, Hongwoo; Kim, Hongjoon
ABSTRACT In this study, we perform a low‐power wireless power transfer experiment to efficiently transfer energy using a phased array antenna (PAA). At the transmitting end, we used a 4 × 4 PAA consisting of left‐handed transmission line‐based compact phase shifters and inset‐feed microstrip patch antennas. The PAA used has a −30° to 30° tilting beam range with a gain ranging from 6.42 to 7.09 dBi. At the receiving end, we used an 8.9‐dBi single Yagi‐Uda rectenna at a distance of 0.8 m from the PAA and measured the converted DC powers to be between 1.5–2.2 mW for the tilting beam range. In the experiment, we limited the effective isotropically radiated power to 3 W because of concerns regarding human body safety. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:421–424, 2015